Inovasi Fintech Syariah dalam Pembiayaan Mikro: Solusi Digital untuk Pemberdayaan Ekonomi - Amelia Nur’aeni (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Innovation in sharia-based financial technology (sharia fintech) provides solutions to challenges in the microfinance sector, especially for micro, small, and medium enterprises (MSMEs) who have difficulty accessing conventional financial services. This study aims to analyze the role of sharia fintech in microfinance and its impact on economic empowerment. The method used is a qualitative descriptive analysis through literature studies, which includes a review of sharia fintech platforms operating in Indonesia. The results of the study show that sharia fintech has succeeded in providing easier and more transparent access to financing for MSMEs with the principle of risk sharing, which supports financial inclusion. Sharia fintech also increases the competitiveness of MSMEs and encourages economic growth. However, challenges related to regulation, financial literacy, and data security still need to be overcome to maximize the potential of sharia fintech. This study concludes that sharia fintech is an effective digital solution in supporting economic empowerment in Indonesia.